In other words thinking Christianly about English language in the curriculum - Hill, Brian (Sydney, NSW Australian Teachers' Christian Fellowship, 1980)
Includes bibliographical references.
Donated by the Australian Teachers' Christian Fellowship, residents of Emmaus Bible College, March 2004.
Keywords: English teaching -- religious aspects -- Christianity; Teaching -- religious aspects -- Christianity